ABO, Lewis, secretor and non-secretor phenotypes in patients infected or uninfected by the Helicobacter pylori bacillus - Mattos, Luiz Carlos de (2002)
CONTEXT: Epidemiological studies have demonstrated higher frequencies of the O blood group and the non-secretor phenotype of ABH antigens among patients suffering from peptic ulcers. Since Helicobacter pylori has been established as the main etiological factor in this disease, contro-versies about the associations of the ABO and Lewis blood group phenotypes and secretor and non-secretor phenotypes in relation to susceptibility towards infection by this bacillus have been presented. OBJECTIVE: To verify the frequencies of ABO, Lewis blood group phenotypes, secretor and non-secretor phenotypes in patients infected or uninfected by H. pylori. DESIGN: Cross-sectional study. SETTING: Outpatient clinic. PARTICIPANTS: One hundred and twenty patients with dyspeptic symptoms who underwent endoscopy. MAIN MEASUREMENTS: ABO and Lewis blood group phenotypes were determined by a standard hemagglutination test and the secretor and non-secretor phenotypes were evaluated by saliva samples using the inhibitor hemagglutination test. RESULTS: The diagnosis of infection, made via breath and urea tests and confirmed using polymerase chain reaction (PCR) in gastric biopsy fragments, showed the presence of H. pylori in 61.7% of the patients and absence in 38.3%. The differences between the frequencies of the ABO blood group phenotypes among infected (A 27.0%; B 12.2%; AB 4.0% and O 56.8%) and uninfected patients (A 58.7%; B 13.0%; AB 4.3% and O 24.0%) were significant. The Lewis blood type, secretor and non-secretor phenotypes showed homogeneous distribution between the groups of patients analyzed. CONCLUSIONS: Our results suggest that the infection of H. pylori can be related to ABO blood groups but not to the Lewis blood group nor to secretor and non-secretor phenotypes.